IMPROVING ВUSINESS РROCESS МANAGEMENT IN UKRAINE - Kosenko, Alisa; Vanina, Yana (Pressing Problems of Public Administration, 2021)
The paper considers the issues related of business рrocess мanagement in Ukraine. The essence of management based on business processes and enterprise benefits from its implementation are considered and analyzed. The current state of the economy is found to be characterized by low innovation activity, so it is necessary to redesign business processes at enterprises. In the modern world, the topic of improving business process administration is quite relevant and plays an important role in the organization’s management system. An important task in the activity of any enterprise is to organize an effective management system that can provide the necessary competitiveness in a market economy. The administration system itself is central to the enterprise; improving business process management can provide the company with a rapid response to changing market conditions, with allowable (minimal) costs. The classification of trade enterprise business processes has been developed. The basis for the classification of business processes contains four basic categories such as: core business processes, support business processes, business development processes and auxiliary business processes. The necessity of forming a mechanism for improving business processes has been proved, which, under conditions of uncertainty, allows adapting the system of management of trade businesses to changes in the external environment. The article also addresses the issue of reengineering logistics processes at the enterprise as a necessary measure for the effective implementation of modern tools for optimizing logistics processes, in the context of introducing the strategic concepts of logistics management systems previously mentioned. The authors provided practical recommendations to domestic enterprises on optimization of logistics systems, the main of which is the formation of a flexible industrial structure of the enterprise, direct orientation of enterprise management to meet the needs of the end user, organization of continuous process of product quality control and the high-level formation of corporate culture at all levels of management of the organization. Effective business process management is one of the key areas of innovation and improvement of enterprises.